ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI GARAM DI KABUPATEN KARANGASEM - Sri Rimayanti Ni Putu; Arka Sudarsana (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2019)
Karangasem regency is an area with salt producing potential. This study aims to determine the effect of capital variables, pond area variables and variable of labor and its influence on production and income of salt farmers in Karanagsem Regency. The results of analysis using path analysis, it states that the capital gives effect to the production and income on salt farmers in Karangasem regency. The results of the analysis for the pond area affect the yield and income of salt farmers in Karagasem Regency. The results of the analysis for the labor force give effect to the production and income on salt farmers in Karangasem regency. The salt farmers are advised to need a coaching program from the government of Karangasem Regency to socialize the salt farmers in order to achieve the production target of iodized salt according to SNI. In order for salt produced by salt farmers in Karangasem regency will be able to compete outside the island of Bali.